Sales Promotion in Marketing Communications. Psychological Characteristics of the Best Public Speakers - Trojanowski , Mariusz (Studia Oeconomica Posnaniensia, 2017)
Personal presentations conveying specific marketing content are part of personal promotion. Presenting in front of a group rather than one person has its own character, burdened with greater stress and hence more difficult. The purpose of the article is to check whether the psychological characteristics of public speakers, including a description of personality traits and a description of self-esteem, remain in relation to their presentation skills. The conclusions offered in the article are based on the results of a study carried out on a sample of 439 representatives of various commercial, manufacturing and service companies. Respondents filled out a questionnaire to diagnose their psychological traits. Then, they were divided into "better" and "other" presenters on the basis of views expressed by their supervisors or HR staff. The analysis of the psychological characteristics, including the personality and self-evaluation of the surveyed employees, showed significant differences between the two groups. The "better" presenters were more open to experience, had a positive attitude and demonstrated conscientiousness. Less important characteristics included such variables as extraversion and empathy. It has also been found that better-performing individuals have higher self-esteem compared to those who perform worse in public speaking, although the level of aspirations was comparable in both groups.